An investigation of the effectiveness of vibration-reducing gloves for controlling vibration exposures during grinding handheld workpieces. (September 2021) - Xu, Xueyan S.; Welcome, Daniel E.; McDowell, Thomas W.; Warren, Christopher; Service, Samantha; Lin, Hansheng; Chen, Qingsong; Dong, Ren G.
Abstract: Prolonged and intensive vibration exposures during the grinding of handheld workpieces may cause hand-arm vibration syndrome. The objectives of this study are to develop an on-the-hand method for evaluating vibration-reducing (VR) gloves, and to determine whether VR gloves can significantly reduce the vibration exposures. A worker holding and pressing a typical workpiece (golf club head) against a grinding wheel or belt in order to shape the workpiece was simulated, and the input vibration and those on the workpiece and hand-arm system were measured. Ten human subjects participated in the experiment. The results demonstrate that VR gloves significantly reduced the vibrations at the palm, hand dorsum, and wrist. The grinding interface condition and hand feed force did not substantially affect glove effectiveness. The use of gloves slightly increased the workpiece resonant response, but the resonant response did not significantly affect glove effectiveness. This study concluded that the use of VR gloves can help control vibration exposures of workers performing grinding of handheld workpieces. Highlights: Developed a method for assessing vibration-reducing (VR) glove effectiveness. Assessed the VR glove effectiveness in the grinding of a handheld workpiece. The VR glove significantly reduced the vibration on the hand dorsum and wrist. The VR glove reduced little vibration on the forearm and upper arm. The hand feed force did not substantially affect the VR glove effectiveness.